Penggunaan Metode Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Indonesia Siswa Kelas V SD Negeri 008 Pulau Lancang - Arabi, Taufik (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
In the teaching and learning process the teacher plays an important role, the teacher must be able to choose the appropriate method. This study aimed to determine the improvement of Indonesian language learning outcomes in the subject matter of folklore offifth grade students at SD Negeri 008 Pulau Lancang. The study was conducted by using the STAD type cooperative method, which each cycle consists of four stages of planning, implementation, observation, and reflection. The subject of this research was fifth grade students. The results of the study using the STAD type cooperative method in learning Indonesian showed the involvement and activeness of students. Learning outcomes that obtained by students also increase in Cycle 1 and Cycle 2. From the data collection obtained learning outcomes in learning in cycle 1 was 73% of students completed learning, while cycle 2 learning outcomes became 100% students completed learning. Based on the results of the study, it can be concluded that the use of the STAD type cooperative method can improve the learning outcomes of fifth grade students of 008 at SD Negeri 008 Pulau Lancang on Indonesian subjects.